(untitled) (Linguamática, 2025)
Although many believe that translating a culinary recipe is a straightforward task, translators face various challenges when undertaking this endeavor—from searching for lexical equivalents to navigating cultural nuances. A particularly useful reference source is a parallel corpus, that is, texts in one language alongside their respective translations. The culinary CorTrad, launched in 2008 as a partnership between Comet and Linguateca, has fulfilled this role, enabling various types of research. It consists of recipes from a book originally written in Portuguese, accompanied by their English translations. In this article, we present a new culinary corpus, CulBras, made up exclusively of Brazilian recipes originally written in Portuguese and their respective translations into English, totaling around 120,000 words in each language. The process of building this corpus is described in detail, as are several possible research avenues using both corpora, including comparisons between them. We invite readers to savor CulBras.